Pemanfaatan Limbah Electroplating Pada Campuran Beton Aspal - Perpustakaan UGM, i-lib ([Yogyakarta] : Jurusan Fisika FMIPA UGM, 2004)
ABSTRACT Metal plating process â to protect metal from rust â produces Electroplating waste (LEp). It must be discarded properly or, otherwise, it can be utilized. Asphaltic concrete is one of flexible pavement material types that commonly use stone dust as filler. The objective of this research is to find the possibility to use LEp as the filler substituting stone dust as the filler in asphaltic concrete mixture. The substitution of stone dust with LEp is done based on the stone dust volume and weight. The asphaltic concrete for wearing course of Directorate General of Regional Infrastructure Development 2000 specification, based on the Marshall method, is used. Result of this research show that the use of LEp as stone 'dust substitute is in comply with the specification, which is at 4% - 6% stone dust substitution (for substitution based on the weight), and 6% - 7% (based on the volume). The engineering properties changing of the asphalt and LEp mixture is also presented in this research. Key words: limbah electroplating, beton aspal